2019
DOI: 10.1111/jppi.12275
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Support Needs in 24/7 Online Support for People With Mild Intellectual Disabilities

Abstract: Service organizations for people with intellectual disabilities (ID) increasingly look for technological applications to improve their services. DigiContact is an online support service developed by Philadelphia Care Foundation in the Netherlands which enables independently living people with ID to contact specially trained support workers 24/7. The purpose of this study was to explore the support needs for which people with ID use online support. We first conducted interviews with 21 individuals with ID who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In a previous study, we found that DigiContact was often used to ventilate worries and frustrations with an aim to relieve oneself of them (Zaagsma et al . 2019). A lack of accessible information on the virus and the containment measures (Courtenay and Perera 2020) may also have contributed to the increase in unplanned online support use as, especially during the first weeks, people with ID were left with questions that caused them to contact the service.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that DigiContact was often used to ventilate worries and frustrations with an aim to relieve oneself of them (Zaagsma et al . 2019). A lack of accessible information on the virus and the containment measures (Courtenay and Perera 2020) may also have contributed to the increase in unplanned online support use as, especially during the first weeks, people with ID were left with questions that caused them to contact the service.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although less frequently, eHealth was also used in other functions, for instance as a self‐supportive tool and for the provision of remote professional contact. It would be beneficial for future eHealth applications to focus on these functions, too, especially because of their potential to empower people with mild intellectual disability and fine‐tune their personal needs in their own environment (Den Brok & Sterkenburg, 2015; Wennberg & Kjellberg, 2010; Zaagsma, Volkers, Schippers, Wilschut, & van Hove, 2019). These eHealth applications could contribute to important issues in the lives of people with mild intellectual disability, such as making their own choices in various domains in life, enhanced independent functioning and being an active member of society (Carey, Friedman, & Nelson Bryen, 2005; Haight et al, 2013; Wehmeyer et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, it is important to emphasise that people with ID living in supported community settings often need support with tasks related to daily functioning in order to meet their personal needs (Thompson et al, 2009). Usually this support is provided through onsite support staff (Stancliffe & Lakin, 2007), yet eHealth can have several potential benefits as an alternative (Taber-Doughty et al, 2010;Zaagsma, Volkers, Schippers, Wilschut, & Van Hove, 2019). That is, support for daily functioning delivered through eHealth can be more focused, targeted and specific because it is offered as needs arise rather than regardless of immediate needs (Perry et al, 2009).…”
mentioning
confidence: 99%
“…However, before further examining the effectiveness of eHealth in support for daily functioning for service users with ID, it is essential to explore the expectations and perceptions of relevant stakeholders towards eHealth in support for daily functioning, as these factors are vital in the successful use of eHealth (Clifford Simplican, Shivers, Chen, & Leader, 2018;Oudshoorn, Frielink, Nijs, & Embregts, 2020;Ramsten, Martin, Dag, & Marmstål Hammar, 2019;Wennberg & Kjellberg, 2010;Zaagsma et al, 2019). Obviously, the expectations and perceptions of service users themselves are imperative for the actual use of eHealth in support for daily functioning.…”
mentioning
confidence: 99%
See 1 more Smart Citation